Addressing inherited predisposition for breast cancer in transplant recipients. Issue 6 (10th February 2016) - Yang, Rachel L.; Kurian, Allison W.; Winton, Lisa M.; Weill, David; Patel, Kapilkumar; Kingham, Kerry; Wapnir, Irene L.
Abstract : Consideration of prophylactic mastectomy surgery following transplantation requires complex medical decision‐making, and bias against elective surgery exists because of concern for post‐operative complications. Prevention of cancer in transplant recipients is of utmost importance, given the risks of treating malignancy in an immunosuppressed patient. We present a patient case and review of the literature to support a thorough pre‐transplantation evaluation of family history and consideration of prophylactic interventions to safeguard the quality of life of transplant recipients. J. Surg. Oncol. 2016;113:605–608 . © 2016 Wiley Periodicals, Inc.